Recaudación de Impuesto y Tasas Municipales del GAD Municipal San Francisco de Puebloviejo - Vera Angamarca, Evelyn Mariana (2018)
The Autonomous Decentralized Governments GAD in Ecuador, are organizations that have administrative, financial and political independence, and are guided towards the rules of solidarity, equality, interterritorial, incorporation and collaboration of citizens. These are formed as follows: GAD Cantonales, GAD Parroquiales, GAD Provinciales, GAD Regionales. These are governed by the Constitution of the Republic of Ecuador, the Organic Code of Territorial Organization, Autonomy and Decentralization and the National Plan for Good Living. From the previous Presidency of the Economist Rafael Correa Delgado which gave a total revolution to the Country promoting the tax culture by all means of communication to the Ecuadorian citizens on the benefit that would be obtained from the collection of taxes and fees for the services that The State lent to the company, together with the SRI (Internal Revenue Service), drew up the necessary plans in order to collect those values ​​for use in works and improvements in Ecuador, although the deferred deficit is evident in the sectional governments, in the which is a great problem at the moment of collecting those taxes that are of its competence. The Municipal Decentralized Autonomous Government of San Francisco de Puebloviejo is in charge of the collection of taxes and fees of the Puebloviejo canton and of the San Juan Rural Parish, in the Financial Management Directorate we find the Treasury area in charge of the collection of these values ​​which are entered to obtain their self-management, each income of securities that are canceled by the citizens is directed to a specific item, where the little commitment of the payment of these items that the users acquire is bringing as a consequence